Could Ergonomics of Portable Oxygen Cylinders Prevent Wastage? Comparison of Two Delivery Devices - Bodier-Montagutelli Elsa; Maréchal Antonin; Porcher Richard; Remérand Francis; Respaud Renaud (De Gruyter, 2016)
Objectives: Ambulatory oxygen therapy is sometimes needed when transferring inpatients. The prescribed administration rate must be maintained during the entire transit time. This implies that paramedical staff calculates the volume of gas remaining in the cylinder, based on the residual pressure displayed on the oxygen cylinders. This step carries a risk of errors and wastage. The objective of this study was to assess the impact of a digital autonomy display system on the use of oxygen cylinders at the hospital.